Stakeholders’ Perceptions on Supplementary English Classes to Basic-Level Students - Gyawali, Ganga Kumari; Kandel, Rajan Kumar (Mangal Research Journal, 2025)
Nepali school education has long faced a significant gap in students’ English language proficiency, largely due to variations in how English is taught—either as a compulsory subject or as a medium of instruction—along with several contextual challenges. Many remote community schools have introduced supplementary English classes to help basic-level learners improve their proficiency. This study aimed to explore the perceptions and experiences of head teachers, English language teachers, students, parents, and school management committee chairs regarding supplementary English classes in basic-level community schools of Nepal. Guided by a phenomenological design within an interpretative paradigm, the study purposively selected ten participants from two community schools in Birendranagar Municipality. Semi-structured interviews were conducted, audio-recorded, transcribed, and thematically analyzed. Findings indicate that supplementary English classes are viewed as highly beneficial, especially for students with weak English backgrounds. These classes provided additional time, practice, and feedback, enabling learners to reinforce classroom learning and reduce language-related difficulties. Stakeholders emphasized that such classes should be institutionally supported and funded by the local government to ensure equitable access. The study suggests that supplementary English classes can help bridge English language proficiency gaps in low-resourced community schools. It highlights the need for policy-level and institutional support to sustain such initiatives and reduce socio-cultural and linguistic disparities among schools and students.